Pedotransfer Function for the Brunswick Soil Hydraulic Property Model and Comparison to the van Genuchten‐Mualem Model. Issue 9 (12th September 2020) - Weber, Tobias K. D.; Finkel, Michael; da Conceição Gonçalves, Maria; Vereecken, Harry; Diamantopoulos, Efstathios
Abstract: Modeling soil hydraulic properties requires an effective representation of capillary and noncapillary storage and conductivity. This is made possible by using physically comprehensive yet flexible soil hydraulic property models. Such a model (Brunswick [BW] model) was introduced by Weber et al. (2019, https://doi.org/10.1029/2018WR024584 ), and it overcomes some core deficiencies present in the widely used van Genuchten‐Mualem (VGM) model. We first compared the performance of the BW model to that of the VGM model in its ability to describe water retention and hydraulic conductivity data on a set of measurements of 402 soil samples with textures covering the entire range of classes. Second, we developed a simple transfer function to predict BW parameters based on VGM parameters. Combined with our new function, any existing pedotransfer function for the prediction of the VGM parameters can be extended to predict BW model parameters. Based on information criteria, the smaller variance of the residuals, and a 40% reduction in mean absolute error in the hydraulic conductivity over all samples, the BW model clearly outperforms VGM. This is possible as the BW model explicitly accounts for hydraulic properties of dry soils. With the new pedotransfer function developed in this study, better descriptions of water retention and hydraulic conductivities are possible. We are convinced that this will strengthen the utility of the new model and enable improved field‐scale simulations, climate change impact assessments on water, energy and nutrient fluxes, as well as crop productivity in agroecosystems by soil‐crop and land‐surface modeling. The models and the pedotransfer function are included in an R package spsh (https://cran.r‐project.org/package=spsh). Plain Language Summary: Soil hydraulic property models are mathematical functions, which describe the relationship between the soil water pressure head and the state of soil water saturation, on the one hand, and the soil water pressure head and the unsaturated soil hydraulic conductivity, on the other. These types of mathematical functions are flexible by adjustable parameters. With one set of model equations, the hydraulic properties of soils which may have very different properties due to their vast natural variability can be described. The models treated in this work are (i) the van Genuchten‐Mualem model, a model with well‐known problems, but still frequently applied, and (ii) a relatively new physical comprehensive model, named the Brunswick model. First of all, in a data‐based comparison of model performance, we demonstrate that the Brunswick model has systematic advantages. Second, knowledge about these above‐mentioned parameters can be determined through other mathematical functions, so‐called hydro‐pedotransfer functions, which empirically relate these parameters to observed soil properties. The information about these soil properties can be measured in the laboratory and is also recorded in soil maps. We created a new pedotransfer function to facilitate the prediction of model parameters for the new Brunswick model. Key Points: A pedotransfer function is established to relate van Genuchten‐Mualem (VGM) to Brunswick (BW) soil hydraulic property model parameters The BW model overcomes the structural deficiencies in VGM and leads to considerably better descriptions of retention and conductivity data With the new pedotransfer function, soil properties and information in soil maps can be used to predicted BW model parameters